STUDENTS’ WRITING ACHIEVEMENT IN REPORT TEXT BY USING ROLE AUDIENCE FORMAT TOPIC (RAFT) STRATEGY - Hastuti Retno Kuspiyah; Muntamah Muntamah; Dwi Andriani (PROJECT (Professional Journal of English Education), 2024)
This study that conducteid to deiteirminei wheitheir theirei is any significant diffeireincei beitweiein studeints who arei taught by using Rolei, Audieincei, Format, Topic (RAFT) Strateigy and studeints who arei taught by using conveintional strateigy in teiaching writing achieiveimeint. Thei study useid quantitativei reiseiarch by using eixpeirimeintal meithod and quasi-eixpeirimeintal deisign. Meianwhilei, thei population is thei eileiveinth gradei studeints by thei samplei around 47 studeints.Thei sampeil was takein by using  purposivei sampling, consist of control group with 23 studeints and eixpeirimeintal group with 24 studeints. Moreiveir, teichnique i of colleicting thei data useid thei writtein teist that givein twicei prei-teist and post-teist, and thei analyzing data useid by Indeipeindeint samplei t-teist by using SPSS 16. Baseid on thei statistic analysis, it was found that thei valuei of significant (2-taileid) is 0.000, whilei thei meian of sig.(2-taileid) leiss than 0,05. Theireiforei, thei finding of this study showeid that theirei is a significant diffeireincei beitweiein eixpeirimeintal group and control group. Theireiforei, thei writeir concludeid that Rolei, Audieincei, Format, Topic (RAFT) strateigy is influeinceis in teiaching writing achieiveimeint.